S3-Leitlinie: Diagnostik und Therapie des hepatozellulären Karzinoms : Kurzversion 2.00 - Juni 2021 - AWMF-Registernummer: 032-053OL - Voesch, Sabrina; Michael, Bitzer; Jörg, Albert; Peter, Bartenstein; Wolf, Bechstein; Susanne, Blödt; Thomas, Brunner; Frank, Dombrowski; Matthias, Evert; Markus, Follmann; Christian, La Fougère; Paul, Freudenberger; et al. (Zeitschrift für Gastroenterologie, 2022)
Thieme E-Books & E-Journals
Gesehen am 07.02.2023